Changes in function and temporal variation in a guild of gall‐parasitoids across a temperature gradient in Australian subtropical rainforest. (6th July 2015) - Hall, Casey R.; Burwell, Chris J.; Kitching, Roger L.
Abstract: Parasitoids play an important role in ecosystem functioning through their influence on herbivorous insect populations. Theoretical and experimental evidence suggest that increased species richness can enhance and stabilize ecosystem function. It is important to understand how richness‐driven functional relationships change across environmental gradients. We investigated how temperature affected the relationship between parasitoid richness and parasitism rate in a guild of gall‐parasitoids along an elevational gradient. We collected galls at 15 sites along five elevational gradients (between 762 m and 1145 m asl) on six occasions over a year. A total of 1902 insects, including 1593 parasitoids, were reared from 12 402 galls. Parasitism rate increased significantly with temperature on all sampling occasions, except December and February. We found a significant, positive richness–parasitism relationship. This relationship, however, was weaker at higher elevations which may be linked to decreased functional efficiency of parasitoids at lower temperatures. Temporal variability in parasitism rate and parasitoid richness were significantly related, regardless of temperature. A stable functional guild of this kind may provide a more reliable ecosystem service under environmental changes.